2017
DOI: 10.3390/s17092127
|View full text |Cite
|
Sign up to set email alerts
|

Response Characteristics and Experimental Study of Underground Magnetic Resonance Sounding Using a Small-Coil Sensor

Abstract: Due to its unique sensitivity to hydrogen protons, magnetic resonance sounding (MRS) is the only geophysical method that directly detects water and can provide nondestructive information on subsurface aquifer properties. The relationship between the surface MRS signal and the location and characteristics of aquifers using large-coil (typically 50–150 m) sensors has been discussed based on forward modelling and experiments. However, few researchers have studied underground MRS using a small-coil sensor. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…MSE is inversely proportional to f s H . The experiments show that the sparse reconstruction of rectangular method is feasible to suppress random noise, and Equations (7) and (8) are verified.…”
Section: Sparse Reconstruction Simulationmentioning
confidence: 79%
See 1 more Smart Citation
“…MSE is inversely proportional to f s H . The experiments show that the sparse reconstruction of rectangular method is feasible to suppress random noise, and Equations (7) and (8) are verified.…”
Section: Sparse Reconstruction Simulationmentioning
confidence: 79%
“…The development of nuclear magnetic resonance imaging in the biomedical field has promoted the MRS application in water resources exploration [4,5]. So far, the MRS method and instrument have been further researched and developed in many countries such as France, the United States, Germany, China and other countries [6][7][8]. The MRS method has been applied to hydrological investigation, observation of permafrost thaw, monitoring the cavity in glacier, water-induced disaster 2 of 32 detection, and infiltrating water surveys [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, their subsequent study also succeeded in obtaining the UMRS signals of a water body 2–12 m using a 6 m × 8 m antenna in front of the Changsongling tunnel in Jilin Province of China [ 5 ]. In addition, by using a multi-turn-small-coil antenna, Qin et al [ 6 ] conducted a systematic numerical modeling study of UMRS detection using the Shandong University physical test system for tunnel geological prediction, and the obtained results were in good agreement with the known water body structure. However, given that mines have more complex environments than tunnels with, e.g., a higher amount of industrial construction, more complex noise interference, and narrower spaces, there have not yet been any successful cases of applying UMRS to mines.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial MRS instruments, such as GMR (Vista Clara, Santa Clara, CA, USA) and NUMIS (Iris, Orléans, France), are mainly employed for ground applications [ 11 , 12 ] and are often large in size and weight. In recent years, MRS instruments purposed for tunnels and mines have been substantially reduced in size and weight so that they can be used in narrow space environments [ 13 , 14 , 15 ]. Similarly, the most commonly-employed commercial TEM instruments available for underground measurements are the EM-47 (Geonics Limited, Mississauga, ON, Canada) and V8 (Phoenix Geophysics, Scarborough, ON, Canada); these instruments not only have the same problem in terms of size and weight, but they also have limited functionality.Considering this, [ 16 ] developed a combined MRS-TEM instrument based on the similarities between MRS and TEM instruments; consequently, test results demonstrated that their proposed instrument could effectively perform groundwater detection.…”
Section: Introductionmentioning
confidence: 99%